Pengembangan Bahan Ajar Pendidikan Nilai Karakter Anti Korupsi Berbasis Local Wisdom Lampung Piil Pasengiri - Atik Purwasih; Arista Wati (Mathematics Education Study Program, 2025)
This study aims to produce teaching materials for anti-corruption character values based on local wisdom Lampung piil pesenggiri, analyze the feasibility of teaching materials for anti-corruption character values education based on local wisdom Lampung piil pesenggiri developed, and analyze student responses to anti- corruption character values education teaching materials based on local wisdom. local wisdom Lampung piil pesenggiri developed. This research is a development research or known as RnD (Research and Development). The floating model used in this research is the 4D model (Define, Design, Develop, Disseminate). The results of the material expert feasibility test obtained a mean percentage score of 96% with a very feasible category without revision. The results of the feasibility test of media experts obtained a mean percentage score of 96.7% with a very feasible category without revision. The results of the small group trial obtained the results of student responses with a positive response, namely the average percentage score of 90.3% in the very good category. Based on the results of the feasibility test and response, it can be concluded that anti-corruption character values education teaching materials based on local wisdom Lampung piil pesenggiri can be used as teaching materials in anti- corruption character value education learning.